Adolescent female soccer players' soccer-specific warm-up effects on performance and inter-limb asymmetries - Elena Pardos-Mainer; José Antonio Casajús; Oliver Gonzalo-Skok (Termedia Publishing House, 2019)
No studies have assessed whether changes in physical performance and inter-limb asymmetries (ILA) can be achieved with the FIFA 11+ prevention programme in adolescent female soccer players. The aim of this study was to assess the effect of the FIFA 11+ programme compared with a standard warm-up on physical performance and ILA in adolescent female soccer players. Thirty-six adolescent female soccer players were randomly assigned to an experimental (EG; n = 19) or a control group (CG; n = 17). Unilateral/bilateral countermovement jump (CMJ), drop jump (DJ) and horizontal jump tests, two different change of direction tests, an ankle dorsiflexion test, the Y-Balance test (YBT) and inter-limb asymmetries were measured before and after 10 weeks of training. The results revealed no significant group-by-time interactions in the vast majority of variables (p>0.05). Paired t-test revealed significant improvements of the right [effect size (ES):0.56] and left (ES:0.49) CMJ, right (ES:0.74) and left (ES:0.54) DJ (ES:0.74), right (ES:1.27) and left (ES:1.26) posteromedial direction and right (ES:0.89) and left (ES:0.84) posterolateral direction in the YBT in the EG (p < 0.05). Right anterior direction in the YBT and V-cut test were significantly improved in both groups (p<0.05). For inter-limb asymmetry variables, no significant group‑by‑time interactions (ES:0 to 0.93) and an improvement between pre‑ and post-tests (ES:-0.76 to 0.49) were observed. Therefore, the FIFA 11+ programme led to improved unilateral jumping, dynamic balance and reduced lower extremity symmetries of several tests in adolescent female soccer players.